OPTICAL SWITCHING CONTROLLER USING FPGA AS A CONTROLLER FOR OCDMA ENCODER SYSTEM - Jaafar, Anuar; Saffie, Nor Baiyah; Sulaiman, Mohd Hafiz (IJSEA, 2014)
This paper proposed a design of optical switching controller using FPGA for OCDMA encoder system. The encoder is one of the new technologies that use to transmit the coded data in the optical communication system by using FPGA and optical switches. It is providing a high security for data transmission due to all data will be transmitting in binary code form. The output si gnals from FPGA are coded with a binary code that given to an optical switch before it signal modulate with the carrier and transmit to the receiver. In this paper, AA and 55 data were used for source 1 and source 2. It is generated sample data and sent packet dat a to the FPGA and stored it into RAM. The simulation results have done by using software Verilog Spartan 2 programming to simulate. After that the output will produces at waveform to display the output. The main function of FPGA controlling unit is producing sing le pulse and configuring optical switching system.